2021
DOI: 10.1155/2021/4989297
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Accurate Segmentation of Venous Thrombus from Black-Blood Magnetic Resonance Images: A Multicenter Study

Abstract: Objective. Deep vein thrombosis (DVT) is the third-largest cardiovascular disease, and accurate segmentation of venous thrombus from the black-blood magnetic resonance (MR) images can provide additional information for personalized DVT treatment planning. Therefore, a deep learning network is proposed to automatically segment venous thrombus with high accuracy and reliability. Methods. In order to train, test, and external test the developed network, total images of 110 subjects are obtained from three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…43,44 Similarly, ML-based tools have been developed for computer-aided diagnosis of DVT, although the majority utilize MR/CE-MRI or CT-venography, while the most widely employed diagnostic technique is compression ultrasound. [45][46][47][48] Aiming to equip non-specialists to detect DVT, a deep learning approach to compression ultrasound images was developed and externally validated with a negative predictive Bleeding, Thrombosis and Vascular Biology 2024; 3(s1):123 value of 98-99%. The authors also performed a cost analysis of integrating this ML tool into their current diagnostic pathway and estimated the net monetary benefits.…”
Section: Machine Learning Applications For Image Recognition In Venou...mentioning
confidence: 99%
“…43,44 Similarly, ML-based tools have been developed for computer-aided diagnosis of DVT, although the majority utilize MR/CE-MRI or CT-venography, while the most widely employed diagnostic technique is compression ultrasound. [45][46][47][48] Aiming to equip non-specialists to detect DVT, a deep learning approach to compression ultrasound images was developed and externally validated with a negative predictive Bleeding, Thrombosis and Vascular Biology 2024; 3(s1):123 value of 98-99%. The authors also performed a cost analysis of integrating this ML tool into their current diagnostic pathway and estimated the net monetary benefits.…”
Section: Machine Learning Applications For Image Recognition In Venou...mentioning
confidence: 99%
“…To overcome the limitations of the DVT manual analysis, studies have been conducted using various imaging modalities and have shown the potential and e ciency of an AI-based CAD system for DVT diagnosis [8][9][10][11]. Among the image modalities, LECTA was found to be more advantageous-it provided more objective images than US; it is easily accessible and frequently used to provide information about extravascular tissues in the bilateral lower extremities and abdominopelvic region.…”
Section: Introductionmentioning
confidence: 99%